2018
DOI: 10.1525/collabra.131
|View full text |Cite
|
Sign up to set email alerts
|

When Structure Competes with Semantics: Reading Chinese Relative Clauses

Abstract: An ongoing debate in Chinese psycholinguistics is whether subject-relative clauses or object-relative clauses are more difficult to process. The current study asks what happens when structure and plausibility are pitted against each other in Chinese relative clause processing. Chinese relative clause structures and semantic plausibility were manipulated to create both plausible and implausible versions of subject-and object-relative clauses. This method has been used in other languages (e.g., English) to elici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…This could imply that L1 Chinese speakers do not have any default preference for relative clause attachments, not because they are not able to employ syntactic parsing strategies, but because semantics and world knowledge may play a substantial role in their interpretation of relative clauses in the L1. Recent findings by Zhou et al (2018) support this conclusion. Their study indicates that sentence plausibility rather than structure predicts reading times and accuracy when interpreting Chinese object and subject relative clauses.…”
Section: Attachment Preferencesmentioning
confidence: 73%
“…This could imply that L1 Chinese speakers do not have any default preference for relative clause attachments, not because they are not able to employ syntactic parsing strategies, but because semantics and world knowledge may play a substantial role in their interpretation of relative clauses in the L1. Recent findings by Zhou et al (2018) support this conclusion. Their study indicates that sentence plausibility rather than structure predicts reading times and accuracy when interpreting Chinese object and subject relative clauses.…”
Section: Attachment Preferencesmentioning
confidence: 73%
“…In fact, the authors in the original and subsequent papers ( Ferreira et al, 2002 , 2009 ; Ferreira and Patson, 2007 ; Ferreira and Lowder, 2016 ; Goldberg and Ferreira, 2022 ) refer to the ideas of good enough representations, good enough approach, good enough processing, and the notion of good enough production/comprehension, but do not state or claim a theory exactly. Yet, others have referred to it as a theory ( Logačev and Vasishth, 2016 ; Christianson et al, 2017 , 2023 ; Zhou et al, 2018 ; Chmiel et al, 2020 ; Huettig et al, 2020 ; Karimi and Diaz, 2021 ; Lopukhina et al, 2022 ). In other words, there is no presentation of “this is how people process language step-by-step,” but rather a rejection of the idea that we carry out complete, “perfect” processing of language in everyday situations.…”
Section: Discussionmentioning
confidence: 99%
“…The strong animacy effects observed in Experiment 2 highlight the important role of animacy in sentence comprehension. Several studies have reported an influence of animacy on syntactic analysis that can lead to misinterpretation (Christianson & Cho, 2009; Ferreira, 2003; Kolk et al, 2003; Kuperberg et al, 2007; Stoops et al, 2014; Zhou et al, 2018). In the context of our study, the animacy effect could be related in part to agent saliency, wherein comprehenders were evaluating which of the animates would serve as the agent in the syntactic parse.…”
Section: Methodsmentioning
confidence: 99%